Chronicles of the sacred (notes for a future Ethnography) - Miranda Bown, Pablo (2013)
From a "poetic Anthropology" this text deals with the concepts "memory" and "ritual" in the ethnographic work in andean communities in northern Chile. It is, also, an attempt to develop the possibilities of writing about the experience about the fundamental dimension of the sacred.